Climatic controls on the global distribution, abundance, and species richness of mangrove forests. Issue 2 (8th March 2017) - Osland, Michael J.; Feher, Laura C.; Griffith, Kereen T.; Cavanaugh, Kyle C.; Enwright, Nicholas M.; Day, Richard H.; Stagg, Camille L.; Krauss, Ken W.; Howard, Rebecca J.; Grace, James B.; Rogers, Kerrylee
Abstract: Mangrove forests are highly productive tidal saline wetland ecosystems found along sheltered tropical and subtropical coasts. Ecologists have long assumed that climatic drivers (i.e., temperature and rainfall regimes) govern the global distribution, structure, and function of mangrove forests. However, data constraints have hindered the quantification of direct climate–mangrove linkages in many parts of the world. Recently, the quality and availability of global‐scale climate and mangrove data have been improving. Here, we used these data to better understand the influence of air temperature and rainfall regimes upon the distribution, abundance, and species richness of mangrove forests. Although our analyses identify global‐scale relationships and thresholds, we show that the influence of climatic drivers is best characterized via regional range‐limit‐specific analyses. We quantified climatic controls across targeted gradients in temperature and/or rainfall within 14 mangrove distributional range limits. Climatic thresholds for mangrove presence, abundance, and species richness differed among the 14 studied range limits. We identified minimum temperature‐based thresholds for range limits in eastern North America, eastern Australia, New Zealand, eastern Asia, eastern South America, and southeast Africa. We identified rainfall‐based thresholds for range limits in western North America, western Gulf of Mexico, western South America, western Australia, Middle East, northwest Africa, east central Africa, and west‐central Africa. Our results show that in certain range limits (e.g., eastern North America, western Gulf of Mexico, eastern Asia), winter air temperature extremes play an especially important role. We conclude that rainfall and temperature regimes are both important in western North America, western Gulf of Mexico, and western Australia. With climate change, alterations in temperature and rainfall regimes will affect the global distribution, abundance, and diversity of mangrove forests. In general, warmer winter temperatures are expected to allow mangroves to expand poleward at the expense of salt marshes. However, dispersal and habitat availability constraints may hinder expansion near certain range limits. Along arid and semiarid coasts, decreases or increases in rainfall are expected to lead to mangrove contraction or expansion, respectively. Collectively, our analyses quantify climate–mangrove linkages and improve our understanding of the expected global‐ and regional‐scale effects of climate change upon mangrove forests.